2016
DOI: 10.1161/circulationaha.116.022992
|View full text |Cite
|
Sign up to set email alerts
|

Does Previous Transradial Catheterization Preclude Use of the Radial Artery as a Conduit in Coronary Artery Bypass Surgery?

Abstract: AbstrAct:The radial artery (RA) is a commonly used conduit for coronary artery bypass grafting, and recent studies have demonstrated that it provides superior long-term patency rates to the saphenous vein in most situations. In addition, the RA is also being used with increasing frequency as the access point for coronary angiography and percutaneous coronary interventions. However, there has been concern for many years that these transradial procedures may have a detrimental impact on the function of RA grafts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…One older study by Kamiya et al reported significantly lower patency rates of catheterized RAs. Mounsey et al have recently highlighted the lack of clinical evidence and the need for further research on this issue. Our findings lend further support to the advocates of the non‐use of catheterized RAs as grafts during CABG, for at least several months following catheterization …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One older study by Kamiya et al reported significantly lower patency rates of catheterized RAs. Mounsey et al have recently highlighted the lack of clinical evidence and the need for further research on this issue. Our findings lend further support to the advocates of the non‐use of catheterized RAs as grafts during CABG, for at least several months following catheterization …”
Section: Discussionmentioning
confidence: 99%
“…This temporal change in interventional cardiology clinical practice is important since the radial artery (RA) is the second most common arterial graft next to the internal mammary artery in patients undergoing coronary artery bypass grafting (CABG). Even though the right RA is the initial access site for radial catheterization, in >10% of cases the left RA can also be used …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Gaudino and colleagues have demonstrated that transradial catheterization results in both mechanical and inflammatory changes that disrupt endothelial integrity . Previous studies have reported lower patency rates when the radial artery conduit has been used following a recent cardiac catheterization …”
mentioning
confidence: 99%